The Effect of Futures Markets on the Stability of Commodity Prices - Johan de Jong; Joep Sonnemans; Jan Tuinstra (Tinbergen Institute, 2019)
Do futures markets have a stabilizing or destabilizing effect on commodity prices? Empirical evidence is inconclusive. We try to resolve this question by means of a learning-to-forecast experiment in which a futures market and a spot market are coupled. The spot market exhibits negative feedback between forecasts and prices, while the futures market is of the positive feedback type, which makes it susceptible to bubbles and crashes. We show that the effect of a futures market on spot price stability changes non-monotonically with the strength of the coupling between the spot and futures markets. This coupling depends positively on the number of speculators on the futures market and negatively on storage costs, speculator risk aversion, and the volatility of futures prices. In the end we observe a stabilizing effect on spot prices for weakly coupled markets and a destabilizing effect when the coupling with the futures market is strong.
Keywords: G41; D84; G13; 330; Price stability; expectations feedback; commodity futures markets; experimental economics